2008
DOI: 10.1073/pnas.0807920105
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex, handedness, and washing on the diversity of hand surface bacteria

Abstract: Bacteria thrive on and within the human body. One of the largest human-associated microbial habitats is the skin surface, which harbors large numbers of bacteria that can have important effects on health. We examined the palmar surfaces of the dominant and nondominant hands of 51 healthy young adult volunteers to characterize bacterial diversity on hands and to assess its variability within and between individuals. We used a novel pyrosequencing-based method that allowed us to survey hand surface bacterial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
935
8
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 993 publications
(1,020 citation statements)
references
References 36 publications
46
935
8
18
Order By: Relevance
“…The standardization of controllable factors to reduce confounders was not well documented or maybe not performed in most of the included studies. As simple factors including but not limiting of age, ethnicity, environmental factors, soap use, hand‐washing and the use of topical (antimicrobial) agents before sampling have been shown to alter microbial skin communities; documentation of these metadata is essential to draw valid conclusions 5, 8, 12, 60, 61, 79, 80, 81. Multiple methods were used for skin microbiome sampling across the studies (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardization of controllable factors to reduce confounders was not well documented or maybe not performed in most of the included studies. As simple factors including but not limiting of age, ethnicity, environmental factors, soap use, hand‐washing and the use of topical (antimicrobial) agents before sampling have been shown to alter microbial skin communities; documentation of these metadata is essential to draw valid conclusions 5, 8, 12, 60, 61, 79, 80, 81. Multiple methods were used for skin microbiome sampling across the studies (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria (52%), Firmicutes (24%), Proteobacteria (17%) and Bacteroidetes (7%) are the four most abundant species identified on the skin 8. Previous studies have shown that it is not only skin topography that influences microbial colonization, but also a vast range of host‐specific factors including age and sex, and environmental factors such as occupation, clothing choice, antibiotic use, cosmetics, soaps, environmental temperature, humidity, and longitudinal and/or latitudinal variation in UV exposure, which can all contribute to the variability seen in the microbial flora of the skin 9, 10, 11, 12, 13, 14, 15. Moreover, changes or aberrations in the skin microbiome have been implicated in the pathophysiology of numerous skin diseases such as AD and AV 16.…”
Section: Introductionmentioning
confidence: 99%
“…The amplicon library was constructed by pooling approximately equal amounts of the amplification products from individual soil samples. Each sample was quantified and the appropriate volume of the cleaned PCR amplicons was combined as previously described (Fierer, Hamady, Lauber, & Knight, 2008), where the amplification products were normalized in equimolar amounts to produce equivalent sequencing depth from all samples. The composite DNA sample was sequenced using a Genome Sequencer 454 FLX System (Roche 454 Life Sciences, CT, USA) with two lanes used.…”
Section: Methodsmentioning
confidence: 99%
“…2 This assessment was undermined seven years later by Fierer et al 's work, which found that the average human palm harbors at least 150 bacterial species-an order of magnitude greater than previous estimates. 3 A 2009 Science study expanded on this understanding of microbial diversity in skin, showing that forearms and underarms, though located just a short distance apart, are as 'ecologically dissimilar as rainforests are to deserts'. 4 Until quite recently, efforts to characterize the human microbiota, such as those of Chiller, had to rely upon in vitro cultivation of microbial species.…”
Section: The Human Body Is An Ecosystem Of Microbesmentioning
confidence: 99%
“…56,57 Similar variability has also been identified in the skin. 3 These unanticipated discrepancies in microbial inhabitants parallel the variability in presentation of chronic inflammatory disease.…”
Section: Successive Infectionmentioning
confidence: 99%